Desempenho acadêmico dos cursos de Ciências Contábeis das Universidades Federais Brasileiras à luz do ENADE - Melo, Geison Calyo Varela de (2020)
In recent years, the expansion of higher education in Brazil, mainly in federal universities, has caused the need for greater attention to the issue of academic performance in higher education courses, among them, the Accounting course that, during its development in the country, passed by a growing evolutionary process and is still evolving. In this perspective, the general objective of this study is to evaluate the factors determining the academic performance of Accounting Sciences courses at Brazilian Federal Universities. To this end, a descriptive and explanatory study was developed, with a quantitative approach and through documentary research. The sample comprises the Accounting Sciences courses of the Brazilian Federal Universities and the data were collected, mainly, from the Higher Education Census and the ENADE Reports, through the Microdata, as well as from the Lattes Curriculum Platform of the teachers and on the courses electronic portal, that make up the sample, and thus, were treated using Cronbach's Alpha test, descriptive statistics, correlation technique and regression analysis. The statistical model brought together the variable academic performance, as a dependent variable, represented by the student's score in the ENADE exam and the independent variables were distributed into three groups: students (sociodemographic and school profile), teachers (training and professional development) and educational institutions. teaching (institutional support). The results show that the model presented acceptable reliability, the variables analyzed have a correlation considered low or median and there is no presence of multicollinearity and autocorrelation, in addition, the regression model was significant at the level of 1% and resulted in a number of 11,566 comments. It was possible to infer that the academic performance of the analyzed courses, is explained by the sociodemographic variables related to sex, age, color / ethnicity, marital status, paid activity and family income, as well as the variables related to the school profile, such as father and mother, modality and type of high school and hours of study outside the classroom. Regarding the teaching variables, mastery of content in the classroom and teaching teaching methodologies, they proved to be significant and influence academic performance and, finally, academic performance can also be explained by the variables of educational institutions linked to available resources, physical facilities of the institution, aspects of the library and extra-class activities.